Effect modification of the association between temperature variability and daily cardiovascular mortality by air pollutants in three Chinese cities. (November 2017) - Luo, Kai; Li, Runkui; Wang, Zongshuang; Zhang, Ruiming; Xu, Qun
Abstract: There is limited evidence showing the mortality effects of temperature variability (TV) on cardiovascular diseases. The joint effects between TV and air pollutants are also less well-established. This study aims to assess the effect modification of TV-cardiovascular mortality by air pollutants in three Chinese cities (Beijing, Nanjing and Chengdu). Data of daily mortality, air pollutants and meteorological factors from 2008 to 2011 was collected from each city. TV was calculated as the standard deviation of daily maximum and minimum temperatures over exposure days. The city-specific effect estimates of TV on cardiovascular mortality were calculated using a quasi-Poisson regression model, adjusting for potential confounders (e.g., seasonality and temperature). An interaction term of TV and a three-level air pollutants stratum indicator was included in the models. Effect modifications by air pollutants were assessed by comparing the estimates of TV's effect between pollutant stratums and calculating the corresponding 95% confidential interval of the differences. Multivariate meta-analysis was conducted to obtain the pooled estimates. The data showed that TV was associated with increased risk of cardiovascular mortality, especially for longer TV exposure days (0–8 days, TV08). This association was still observed after adjusting for air pollutants on current day or the previous two days. Stronger estimates were observed in females, but no significant difference between males and females was detected, indicating the absence of evidence of effect modification by gender. Estimates of TV-cardiovascular mortality varied across two season periods (warm and cool season) and age groups, but the evidence of effect modification by age and seasons was absent. Regarding the effect modification of TV-cardiovascular mortality association by air pollutants, a significant effect modification was identified for PM10, but not for NO2 and SO2 in the whole population for all TV exposure days. This finding also persisted in subgroups, specifically in females and the elderly. Graphical abstract: Percent increase (95%CI) in cardiovascular mortality associated with 1 ° C increase in TV for the whole population in whole level (without stratums) and three stratums. Results were pooled through meta-analyses of three city-specific estimates. a There exists statistical significant difference in estimates between high and low level of air pollutants. Lag of pollutant was selected on current day. Age groups were defined by setting cut point in age at 65 years old. Highlights: Large change in temperature variability (TV) was an independent risk factor for cardiovascular mortality. Females were more susceptible to the sudden change in temperature variation. The observed TV-cardiovascular-mortality associations were modified by particulate matter (PM10 ), this finding persists in females and elderly.